Tren Penelitian Health Literacy Tahun (2015–2025): Analisis Bibliometrik Menggunakan Publish or Perish dan VOSviewer - Awis Hamid Dani; Cucu Herawati; Nur Arofah; Aniq Alimmuddin (Yayasan Jompa Research and Development, 2026)
Health literacy is an important competency in public health related to an individual's ability to access, understand, evaluate, and use health information in making decisions related to health maintenance, disease prevention, and the utilization of health services. Over the past decade, research on health literacy has grown rapidly and expanded to various dimensions, including digital health literacy and mental health literacy. The increasing number of publications indicates that health literacy has become a significant topic in global health research. This study aims to map the development trends, citation influence, and thematic structure of health literacy research during the period 2015–2025 using a bibliometric approach. This study employed a quantitative bibliometric method using data sourced from Google Scholar. Publication data were collected using the Publish or Perish software with the keyword “health literacy,” and then analyzed using VOSviewer to map keyword relationships through network, overlay, and density visualization. After the data selection and cleaning process, a total of 998 documents were included in the analysis. The findings show that publications on health literacy have experienced an increasing trend, with two major peaks occurring in 2018 and 2020. Network analysis identified four main research clusters covering conceptual and digital aspects, clinical contexts and chronic diseases, mental health literacy among adolescents, and the relationship between health literacy and health outcomes. These findings indicate that health literacy has evolved into a multidisciplinary research field increasingly integrated with issues of digital health, mental health, and health information management.